Особенности акустических характеристик обнаружения малых БПЛА - Усольцев, А. А. (My University, 2018)
In this paper, we consider the acoustic characteristics of detection of small unmanned vehicles. On an example of a monoplane and quadrocopter. The results of the studies are displayed in the spectral diagram.
Keywords: БПЛА; акустическое излучение